Developing entrepreneurial mindset through financial literacy training for educators and parents at adventure school - Andriati Fitriningrum; Andrey Hasiholan Pulungan; Ni Ketut Cahya Deta Saraswati; Samuel Reza Surjadi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Financial literacy is a key focus at Sekolah Alam Kebun Tumbuh in Sawangan, Depok, Indonesia. The school integrates environmental engagement into its teaching and learning processes, aiming to achieve educational goals through positive role models and values. Recognizing the communityâ€™s limited financial knowledge, a primary community development initiative was established to address this gap. This program aims to enhance financial literacy among educators and parents, thereby fostering an entrepreneurial mindset in students. The program begins with the planning and execution of modules, which involve brainstorming and preliminary investigation. The initial phase included an introduction to entrepreneurship, followed by in-depth instruction on fundamental financial concepts and budgeting. Each training session included a pre-test to assess participants' initial skill levels and a post-test to measure progress. Additionally, participants gave presentations to evaluate their understanding post-training. The results indicate a significant improvement in participants' abilities to create financial models. Evaluations show enhanced financial and entrepreneurial skills among the participants. Feedback highlights the need for longer-term program sustainability and greater community involvement.Â